Nano-immunotherapeutics: targeting approach as strategic regulation at tumor microenvironment for cancer treatment - Priyanka Singh; Monika Yadav; Karishma Niveria; Anita Kamra Verma (Open Exploration Publishing Inc., 2022)
Cancer is the leading cause of mortality worldwide, which necessitates our consideration related to novel treatment approach. Tumor cells at the tumor microenvironment (TME), regulate a plethora of key mechanistic signaling pathways that obstruct antitumor immune responses by immune suppression, immune resistance or acquired immune tolerance. The present therapeutic regimes are provided independently or in combination, or as immunotherapies for cancer immune targeting. Immunotherapy has altered the arena of oncology and patient care. By using the host immune system, the immunostimulatory molecules can exert a robust, personalized response against the patient's own tumors. Alternatively, tumors may exploit these strategies to escape immune recognition, and accordingly, such mechanisms represent chances for immunotherapy intervention. Nonetheless, despite promising outcomes from immunotherapies in recurrent and metastatic cancers, immune-therapeutics in clinics have been limited owing to unpredictability in the produced immune response and reported instances of immune-related adverse effects. The unrealized potential of immunotherapies in cancer management maybe due to the obstacles such as heterogeneous nature, multiple targets, patients' immune response, specificity for cancer or variability in response generation in toxicity levels, delivery and cost related to therapeutics etc. Further revolutionary trends related to immunotherapies are noticeable with slower progress for cancer management. Recent advances in nanomedicine strategize to ameliorate the lacuna of immunotherapy as it relies on the inherent biophysical characteristics of nanocarriers: size, shape, surface charge and multifunctionality and exploiting them as first line therapy for delivery of biomolecules, single checkpoint inhibitors and for imaging of TME. Therefore, nano-assisted immunotherapies can boost the immunotherapeutic approach, overcoming factors that are with imminent potential risks related to it, thereby significantly improving the survival rate associated with it in cancer patients. Nanotechnology is anticipated to overcome the confines of existing cancer immunotherapy and to successfully combine various cancer treatment modes.